Mesenteric lipoma simulating an ovarian teratoma - Swati Deshmukh, MD; Florette K. Hazard, MD; Claudia M. Mueller, PhD, MD (Elsevier, 2017)
We present a case of a four-year-old patient who presents with chronic episodic umbilical pain. CT revealed an abdominal mass considered to be ovarian in origin. The real etiology of the patient's pain was found after laparoscopic surgery and pathological analysis, which confirmed the mass to be a mesenteric lipoma. Retrospective coronal reconstruction of the CT demonstrated a mesenteric vessel supplying the lesion. Mesenteric lipoma, although rare in children, should be considered in the differential diagnosis for a fatty pelvic mass.